The Impact of Exports to GDP in Fixed Capital Formation In Iraqi Economy Under the WTO (With Reference to The Kurdistan Region of Iraq) - Akrawi, Zaki M.; Mohamed, Rebar F. (Humanities Journal of University of Zakho, 2015)
Economic variables gaining their degree of importance from the role which play in the future of the country’s economy, so the variable of fixed capital formation is a high importance in the national economy as it provides an investment plan for the country and is considered an indicator of the rational economic plan established for the purpose of reaching its target, and provide statistics about this indicator is an urgent need to develop an integrated economic plan which will reflect the size of production capacities, as well as interventions with other economic variables that can provide, support and contribute to formation the fixed capital by contributing to the development of annual additions of fixed assets. So In this study, econometrics approach was putted to view the relationship and influence that caused by the variable of total Iraqi exports to GDP in support and make additions to capital assets through the index fixed capital formation through the changes in the international foreign accredited in this research, namely the existence of the WTO and its restrictions on business operations, including exports, which was adopted as the basis for one of the variables of the approach in this paper, the results of the statistical analysis showed the presence of non-linear relationship between the independent variable and the dependent variable through the value of correlation coefficient, which was equal to 79%, referring to a strong relationship confirmed its significant by the value of (T) test, which equal to 3.6, which surpassed its tabulated value.